Hepatitis C in immunocompromised pediatric patients: an epidemiological analysis of data from a center of pediatric hematology, oncology and immunology - Satsuk A.V.; Solopova G.G.; Churilova N.S.; Vlasenko N.V.; Panasiuk Ya.V.; Ploskireva A.A.; Akimkin V.G. (Клиническая микробиология и антимикробная химиотерапия, 2021)
Objective.